2021
DOI: 10.1186/s12885-021-08564-3
|View full text |Cite
|
Sign up to set email alerts
|

The combined effect of dichloroacetate and 3-bromopyruvate on glucose metabolism in colorectal cancer cell line, HT-29; the mitochondrial pathway apoptosis

Abstract: Background 5-Fluorouracil (5-FU) is regarded as the first line treatment for colorectal cancer; however, its effectiveness is limited by drug resistance. The ultimate goal of cancer therapy is induction of cancer cell death to achieve an effective outcome with minimal side effects. The present work aimed to assess the anti-cancer activities of mitocans which can be considered as an effective anticancer drug due to high specificity in targeting cancer cells. Method… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…A study by Chen et al, [ 44 ] demonstrated tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) linked apoptosis in human breast cancer cells. In addition, yet another study by Nikravesh et al, [ 48 ] reported that the 3BP treatment significantly induced apoptosis, activation of caspase 3 activity, depolarization of mitochondrial membrane potential and ROS production in colorectal cancer cell line.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Chen et al, [ 44 ] demonstrated tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) linked apoptosis in human breast cancer cells. In addition, yet another study by Nikravesh et al, [ 48 ] reported that the 3BP treatment significantly induced apoptosis, activation of caspase 3 activity, depolarization of mitochondrial membrane potential and ROS production in colorectal cancer cell line.…”
Section: Resultsmentioning
confidence: 99%
“…Synergism has been reported when DCA is combined with different drugs for anti-cancer research: DCA/cisplatin or gefitnib or elotinib ( Al-Azawi et al, 2021 ), DCA/metformin ( Kim et al, 2021 ; Klose et al, 2021 ; Korsakova et al, 2021 ), DCA/3-bromopyruvate ( Nikravesh et al, 2021 ), DCA/sorafenib ( Sun et al, 2021 ), DCA/PX-478 ( Parczyk et al, 2021 ) and DCA/erlotinib ( Dyrstad et al, 2021 ). Said synergistic effect has also been observed when Nic is combined with other agents: Nic/gemcitabine ( Guo et al, 2022b ), Nic/metformin ( Kang et al, 2021 ) and Nic/doxorubicin ( Lohiya and Katti, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…DCA has been shown to elevate hydrogen peroxide ( Xie et al, 2011 ) and ROS ( Kumar et al, 2012 ; Duan et al, 2013 ; Kim et al, 2021 ; Klose et al, 2021 ; Nikravesh et al, 2021 ). In addition, ROS is increased when DCA is combined with sorafenib ( Sun et al, 2021 ) or PX-478 ( Parczyk et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…3-BrPA is an analog of pyruvate with high tumor selectivity ( 28 ). This small alkylating compound can induce cell death through two mechanisms: One involves inhibiting HK2 to prevent the glycolysis process ( 29 ), and the other involves activating the mitochondrial pathway of apoptosis ( 30 ). 3-BrPA functions in a variety of tumor cells, including multiple myeloma cells ( 31 ) and hepatocellular carcinoma cells ( 32 ).…”
Section: Discussionmentioning
confidence: 99%